Innovative approach in adsorption chiller: Combination of condenser-adsorber for improving performance - Ilis, Gamze Gediz; Demir, Hasan; Saha, Bidyut Baran (Pergamon-Elsevier Science Ltd, 2021)
This study aims experimental and numerical investigation of an adsorption chiller having a new combined condenser-adsorbent bed. The designed and manufactured adsorption chiller having a shell and tube type adsorbent bed consisting of 444 tubes of 10 mm inner diameter is simulated. The experimental cycle of the adsorption chiller was successfully obtained. In the numerical study, the influence of desorption temperature and condenser pressure on the performance indicator of adsorption chiller is investigated. In the experimental study, the coefficient of performance of the adsorption chiller is found as 0.80. The system's specific cooling power and volumetric cooling power values were determined as 30 W/kg and 6.7 kW/m(3), respectively. Instantaneous transferred heat from heat exchanger fluid to adsorptive in the evaporator during the isobaric adsorption process reached 0.6 kW between 250 and 350 s. The numerical results showed that the increment of desorption temperature and decreased condensation pressure succeeded in increasing the performance indicators.
Keywords: Adsorption chiller; Embedded condenser; Combined condenser-adsorber; Experimental-numerical comparison